Pelatihan dan edukasi pemanfaatan limbah kulit pisang sebagai bahan aktif pembuatan sabun ramah lingkungan bersama tim PKK di desa Sumberarum Bojonegoro - Lana Fauziah; kusuma pitaloka, Ria indah; Siti Aminah (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This community service activity aims to raise environmental awareness and promote economic independence among the women of the PKK (Family Welfare Movement) in Sumberarum Village, Bojonegoro, through training on utilizing banana peel waste as an active ingredient in the production of environmentally friendly soap. The implementation method consists of five stages: preparation, socialization, training, evaluation, and follow-up assistance for sustainability. The results show a significant increase in participants’ knowledge by 85%, based on pre-test and post-test results, and 90% of participants successfully produced quality soap during the practical session. The participants showed great enthusiasm and have started independent soap production at home. Furthermore, a small business group based on the PKK was established to support the sustainability of the program. This activity demonstrates that organic waste management can serve as an innovative solution for community empowerment and environmental conservation, while also offering potential for development into competitive micro-enterprises.